Роман Джеймса Патріка Донліві «Рудий»: негативна чи позитивна поетика? - Бойченко, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the problems of negative and positive poetics in J. P. Donleavy’s novel «The Ginger Man». The contradictious positions of different scholars are analyzed. The con lusion is made about the dominance of extremely positive energy in the novel.